Modulation of Chloride Channel Functions by the Plant Lignan Compounds Kobusin and Eudesmin - Jiang, Yu; Yu, Bo; Fang, Fang; Cao, Huanhuan; Ma, Tonghui; Yang, Hong (Frontiers in Plant Science, 2015)
Plant lignans are diphenolic compounds widely present in vegetables, fruits and grains. These compounds have been demonstrated to have protective effect against cancer, hypertension and diabetes. In the present study, we showed that two lignan compounds, kobusin and eudesmin, isolated from Magnoliae Flos, could modulate intestinal chloride transport mediated by cystic fibrosis transmembrane conductance regulator (CFTR) and calcium-activated chloride channels (CaCCs) chloride channels. The compounds potentiated CFTR channel function in both FRT cells and in HT-29 cells. The modulating effects of kobusin and eudesmin on the activity of CaCCgie (CaCC expressed in gastrointestinal epithelial cells) were also investigated, and the result showed that both compounds could stimulate CaCCgie-mediated short-circuit currents and the stimulation was synergistic with ATP. In ex vivo studies, both compounds potentiated CFTR and CaCCgie chloride channel activities in mouse colonic epithelia. Remarkably, the compounds showed inhibitory effects toward ANO1/CaCC-mediated short-circuit currents in ANO1/CaCC-expressing FRT cells, with IC50 values of 75 M for kobusin and 100 M for eudesmin. In charcoal transit study, both compounds mildly reduced gastrointestinal motility in mice. Taken together, these results revealed a new kind of activity displayed by the lignan compounds, one that is concerned with the modulation of chloride channel function.